Re-visiting the FDI-led Growth Hypothesis for South Africa: The Role of Industrialization and Urbanization - Joshua, Udi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This study aims at investigating the FDI-led growth hypothesis in the case of South Africa using time series data spanning from 1970 to 2017. The empirical rout begin with the unit root tests using the traditional ADF, PP, and the confirmatory KPSS unit root test as well as the Zivot-Andrew unit root test which accounts for a single structural break. The overall result revealed a mixed order of integration between the series. Given the above outcome, the study employed the dynamic ARDL bounds testing to cointegration which reveals long run equilibrium between the variables of interest. The revelation from the study further proves that FDI inflow asserts a significance positive impact on economic growth both in the short and long run. The dynamic Granger causality test indicates a one-way interaction running from FDI inflow to economic growth which aligns with FDI-led growth hypothesis. In-view of the findings, this study therefore recommends that the South Africa government should shift her attention first, to expanding the absorptive capacity of the South African economy above the standard threshold; this will help in converting FDI inflow to South Africa to its full capacity which will in turn drive economic growth proportionately. Also, the study suggests the formulation of mechanism or measures that will help attract a diversify FDI inflow to other sectors of the economy such as manufacturing, agriculture with the aim of achieving training and technology transfer in other to harness the spillover effect of FDI inflow on the economy as a whole. Keywords: Foreign Direct Investment, Economic Growth, Industrialization, Urbanization

ÖZ: Bu çalışma, Güney Afrika ‘da doğrudan yabancı yatırım (DYY) kaynaklı büyüme hipotezini 1970'den 2017'ye zaman serisi verilerini kullanarak incelemeyi amaçlamaktadır. Ampirik çalışmada, geleneksel ADF, PP ve doğrulayıcı KPSS birim kök testlerinin yanında tek bir yapısal kırılmayı dikkate alan Zivot-Andrew birim kök testi kullanılmıştır. Birim kök testlerinin genel sonucunda, serilerin durağanlık derecelerinin karışık olduğu ortaya çıkmıştır. Bu sonuç çerçevesinde, çalışmada ilgili değişkenler arasında uzun dönem ilişkisini araştırmak için dinamik Otoregresif Dağıtılmış Gecikme Modeli (ARDL) kullanılmıştır. Elde edilen bulgular, DYY’ nin hem kısa hem de uzun dönemde ekonomik büyüme üzerine pozitif etkisi olduğunu göstermiştir. DYY kaynaklı büyüme hipotezi doğrultusunda, Dinamik Granger nedensellik testi sonucuna göre DYY girişinden ekonomik büyümeye tek yönlü Granger nedensellik ilişkisi bulunmuştur. Ampirik bulgulara göre, bu çalışma, Güney Afrika hükümetinin önce Güney Afrika ekonomisinin emici kapasitesini standart eşiğin üstünde genişletmeye odaklanmasını önermektedir. Bu, Güney Afrika’da DYY girişinin tam kapasiteye dönüştürülmesine yardımcı olacaktır ve bunun sonucunda ekonomik büyüme sağlanmış olacaktır. Ayrıca, bu çalışma, DYY akışının ekonominin bütününe yayılma etkisinden yararlanmak için eğitim ve teknoloji transferini sağlamak amacıyla üretim, tarım gibi ekonominin diğer sektörlerine çeşitlendirilmiş bir DYY girişini çekmeye yardımcı olacak mekanizma veya önlemlerin oluşturulmasını önermektedir. Anahtar Kelimeler: Doğrudan Yabancı Yatırım, Ekonomik Büyüme, Sanayileşme, Kentleşme.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2019. Supervisor: Assoc. Prof. Dr. Hasan Güngör.
Keywords: Economics; Economic Conditions and Development--Economic Growth--Investments--South Africa; Foreign Direct Investment; Economic Growth; Industrialization; Urbanization